Influence of oxygen atmosphere on LiNbO3 thin films prepared by Pechini process - Stojanovic, B. D.; Simões, A. Z. [UNESP]; Zaghete, M. A. [UNESP]; Setter, N.; Varela, José Arana [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2004)
Thin films of lithium niobate were deposited on the Pt/Ti/SiO2 (111) substrates by the polymeric precursor method (Pechini process). Annealing in static air and oxygen atmosphere was performed at 500°C for 3 hours. The films obtained were characterized by X-ray diffraction, scanning electron microscopy and transmission electron microscopy. The dielectric constant, dissipation factor and resistance were measured in frequency region from 10 Hz to 10 MHz. Electrical characterizations of the films pointed to ferroelectricity via hysteresis loop. The influence of oxygen atmosphere on crystallization and properties of LiNbO3 thin films is discussed.
Keywords: Annealing; Chemical vapor deposition; Data reduction; Epitaxial growth; Ferroelectric materials; Grain boundaries; Lithium niobate; MIM devices; Polarization; Positive ions; Sol-gels; Stoichiometry; Transmission electron microscopy; X ray powder diffraction; Atmosphere flow; Electrooptical; Ion distribution; Pechini process; Thin films